Uniwersum poetyki. Prolegomena - Szczęsna, Ewa (Załącznik Kulturoznawczy, 2021)
The article analyzes the influence of semiotic systems typical of various artistic discourses on the poetics of the text (especially the modeling of rhetorical figures) and the creation of textual meanings. The thesis put forward is that the comparative characterization of textual forms makes it possible, on the one hand, to extract universal mechanisms of creating meanings (constitutive features of figures – ‘genetic information’ of poetics), and on the other hand, to examine their many representations that determine the multivariance of poetics. Migrations of figure variants from one discursive environment to another cause a ‘semantic explosion’ and determine the development of discursive forms and, as a result, the dynamics of culture. This issue is shown on the example of the forms of an ellipse in art – the ways of realizing the unsolvable and solvable concealment in literature and film. Literary and cinematic procedures are analyzed, which transform the grammatical and rhetorical ellipse into an artistic strategy.